Design Method of Smart City Public Planning under the Constraint of Public Acceptability - Ben Pi; Pinghui Liu (Advances in Multimedia)
In order to improve the design effect of smart city public planning, this paper studies the design method of urban public planning under the constraint of public acceptability and designs the corresponding intelligent system. Moreover, from the perspective of the planning system and practical application, this paper is devoted to improve the performance of the planning system and expand the application field of planning technology. In addition, this paper analyzes and studies the preprocessing stage and the planning search stage of the planning system and applies its domain knowledge modeling to practical planning problems. The experimental research results show that intelligent public urban planning and design method proposed in this paper under the public acceptable constraints has a good effect.